1974
DOI: 10.2466/pr0.1974.34.3c.1158
|View full text |Cite
|
Sign up to set email alerts
|

Superstitiousness and Intelligence

Abstract: Powers ( 193 1 ) and Belanger ( 1944 ) reported negative correlations between measures of intelligence and measures of superstitiousness in college students, but neither of the correlations was statistically significant. The present report investigated the relationship between an original index of superstitiousness and a widely used test of intelligence.Forty-nine seniors in two classes of a public high school in Georgia, whose ages ranged from 17 to 19 yr., anonymously cook an original 57-item superstitious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Plug's (1976) review of the literature on superstitions found that the majority of the studies were poorly done, out-dated, and conflicted one another. The early literature and the more recent reports of the relationship between age (Wagner, 1928;Thouless and Brown , 1964), sex, (Blum and Blum, 1974), intelligence (Killen et al, 1974), education (Pasachoff et al , 1970), and environment (Blum, 1976) and superstitious beliefs are conflicting and inconsistent. Opie and Opie (1959) have compiled the largest sample of childhood superstitious beliefs surveying 5,000 school children throughout the United Kingdom.…”
Section: Childhood Superstitionsmentioning
confidence: 99%
“…Plug's (1976) review of the literature on superstitions found that the majority of the studies were poorly done, out-dated, and conflicted one another. The early literature and the more recent reports of the relationship between age (Wagner, 1928;Thouless and Brown , 1964), sex, (Blum and Blum, 1974), intelligence (Killen et al, 1974), education (Pasachoff et al , 1970), and environment (Blum, 1976) and superstitious beliefs are conflicting and inconsistent. Opie and Opie (1959) have compiled the largest sample of childhood superstitious beliefs surveying 5,000 school children throughout the United Kingdom.…”
Section: Childhood Superstitionsmentioning
confidence: 99%
“…Within this programme, studies have investigated supposed diåerences between paranormal believers and disbelievers in educational attainment (Emmons & Sobal, 1981 ;Messer & Griggs, 1989 ;Tobacyk, Miller & Jones, 1984), science education (Otis & Alcock, 1982 ;Irwin, 1990 ;Tobacyk, 1983), performance on intelligence tests (Jones, Russell & Nickel, 1977 ;Killen, Wildman & Wildman, 1974) and accuracy in probability judgments (Blackmore & Troscianko, 1985 ;Brugger, Landis & Regard, 1990). For each of these, however, the ®ndings are inconsistent (Blackmore, 1994, summarizes the relevant literature for the last-named ; see Irwin, 1993, for a review of the others), and at best provide only equivocal support for the cognitive de®cits hypothesis.…”
mentioning
confidence: 99%
“…Individuals with more educational achievement are less likely to hold religious paranormal beliefs. The negative relationship between education and paranormal belief is supported by Vyse (1997), Blum (1974Blum ( , 1976, Jahoda (1970), and Killen, Wildman, and Wildman (1974). These findings are at odds with Irwin (1993) who, in a meta-analysis of several studies of paranormal belief research, showed that there was no correlation between paranormal belief and intelligence.…”
Section: No Significant Direct or Indirect Relationship Was Found Betmentioning
confidence: 97%
“…Intelligent or highly educated participants have been shown to have less paranormal beliefs (Blum S. H., 1974;Blum S. H., 1976;Jahoda, 1970;Killen, Wildman, & Wildman, 1974;Mencken, Bader , & Kim, 2009). Killen, Wildman, and Wildman (1974), in addition to Blum (1974;1976), found a inverse relationship between paranormal beliefs and intelligence.…”
Section: Deprivation Modelmentioning
confidence: 99%
See 1 more Smart Citation